A modernidade e suas expressões em Na colônia penal, de Franz Kafka - Senhorini, Hugo Giazzi [UNESP] (2017)
This dissertation aims to discuss expressions of modernity in In the Penal Colony by Franz Kafka. More precisely, it discusses how this literary work explores and critically represents worldly elements such as extreme rationalization, and disorientation of the modern individual. This work is the result of an investigation which works with the hypothesis that it is possible to read Kafka’s narrative as an allegorical representation of modernity itself. The first chapter of this text discusses, based on philosophical and sociological sources, some of the most characteristic phenomena of that which is understood as modernity, in order to eventually formulate a sufficiently stable concept of modernity that may support the subsequent literary analysis. Within this discussion, a concept such as the Disenchantment of the world receives special attention. In addition, modern literature and Modernism are exposed in the first chapter. The second chapter introduces, firstly, a brief critical revision on Kafka’s oeuvre. Subsequently, it presents the reading of In the Penal Colony, which is separated in two parts, or two “levels”. The first level exposes an immanent analysis of the narrative, and its meaningful, more formal elements are outlined, thus creating, through this close-reading process, an array of interpretative elements that are supported by the literary text; in the reading’s second level, the elements outlined by the previous analysis are related and studied in relation to the modern world elements as these have been previously defined. Thus, the second chapter tries to build an interpretation of the narrative that can outline and comprehend, in a cohesive reading, the exploration, expression, and criticism of those modern characteristics made by the literary work. This process verifies that Kafka’s work can, on an interpretative level, express modernity critically, and rebuild it within a complex allegorical construction.